ANALISIS PENGARUH FAKTOR-FAKTOR KUALITAS PELAYANAN RITEL TERHADAP MINAT MEMBELI KONSUMEN PADA RITEL MODERN CARREFOUR DI PONTIANAK - Heng, Lie (MABIS, 2013)
This study is aimed at determining the factors of retail service quality that affect customer purchase decision on the modern retail Carrefour Pontianak. Data were collected with questionnaires techniques which are arranged in the form of a Likert Scale to 150 respondents who are consumers of modern retail Carrefour in Pontianak by purposive sampling technique. Data collected were then processed with the technique of multiple regression analysis. The study of the five dimensions of retail service quality consisting of service personnel, physical aspects, merchandise, confident, and parking, show that the five overall retail service quality dimensions together influence consumer purchasing decisions significantly. Partially, the factors that influence consumer purchasing decisions are the dimension of the physical aspect, confident and parking